Formando psicólogas/os para as relações raciais: avanços e contradições nos cursos de Psicologia da Bahia - Khouri, Jamille Georges Reis (2019)
This research is based on the idea that racism is a fundamental ideology for the understanding of social inequalities in Brazil and the subjective construction of Brazilians, as well as the psychological suffering experienced by black people who are victims of racism. In this way, this research defends the urgency of enabling psychologists to access this debate in order to build antiracist practices and accept this demand. Traditionally, the degree in psychology presents a subject separated from social reality, transforming social problems into individual ones. Currently, it is possible to see changes in this proccess, identifying conceptions that analyze the subject in an integrated way to social reality, in addition to practices that point to a social commitment of this science and profession. It is in the heart of these contradictions that this dissertation is found. The aim of this research is to study the significance of the presence of race relations debates in psychology degree courses in Bahia. To do so, seven interviews were conducted with the coordinators and teachers who are responsible for discussing racial relations in four educational institutions in the State of Bahia. The meanings were analyzed from four thematic axes, being: 1. Achievements; 2. Desired achievements; 3. Factors that hamper progress; 4. Factors that facilitate progress. Even though research demonstrates that it is possible to advance, one should not lose sight of this subject. Racism, traditional and prejudiced conceptions of subject, society, science and psychology, hinder and prevent the consolidation of another project for the degree. Therefore we consider that discussing race relations is urgent, necessary and represents a breakthrough for psychology and for society as a whole, since society - and its subjectivities - can not be understood without the concept of race and racism. We conclude, therefore, that it is only possible to construct a critical and committed psychology with social transformation if it is antiracist, and formation at the higher level is a privileged space for the development of ethical and political positioning